2015
DOI: 10.1093/jee/tov134
|View full text |Cite
|
Sign up to set email alerts
|

Regional-Scale Spatio-Temporal Analysis ofAnastrepha ludens(Diptera: Tephritidae) Populations in the Citrus Region of Santa Engracia, Tamaulipas, Mexico

Abstract: Large citrus areas in Tamaulipas are affected by Anastrepha ludens (Loew) populations. Here we report the findings of a spatio-temporal analysis of A. ludens on an extended citrus area from 2008-2011 aimed at analyzing the probabilities of A. ludens infestation and developing an infestation risk classification for citrus production. A Geographic Information System combined with the indicator kriging geostatistics technique was used to assess A. ludens adult densities in the spring and fall. During the spring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Also, while studying the spatio-temporal dispersion, but of the Anastrepha ludens over large flat topographic citrus areas, Vanoye-Eligio et al (2015) obtained with success the occurrence probability maps for this specie. Rhodes et al (2011) used IDW and OK produced maps with similar accuracy, indicating that "hot spots" could be modeled using either interpolation method.…”
Section: Resultsmentioning
confidence: 99%
“…Also, while studying the spatio-temporal dispersion, but of the Anastrepha ludens over large flat topographic citrus areas, Vanoye-Eligio et al (2015) obtained with success the occurrence probability maps for this specie. Rhodes et al (2011) used IDW and OK produced maps with similar accuracy, indicating that "hot spots" could be modeled using either interpolation method.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there was a reduction in the levels of fruit infestation compared to an area without application of control methods. Vanoye-Eligio et al (2015a, 2015b reported that populations in the region become detectable from October to April, with the highest population peaks in February and March. Such seasonal population peaks did not occur in areas under sterile fly release, which is an indication that the decrease was a result of the application of the sterile insect technique.…”
Section: Discussionmentioning
confidence: 99%
“…The results differ because the A. ludens species was the most abundant species, while in the present study it was A. obliqua, whereas A. ludens was the one with the lowest populations; although, the present peaks are not coincident, the behaviors of insect in both studies are similar. Several authors agree that abiotic factors such as temperature, relative humidity and rainfall have an effect on the population fluctuation of fruit flies (Tucuch et al, 2008;Vanoye-Eligio et al, 2015), while other factors such as food availability and controllers are important for the presence or absence of the pest (Ovruski et al, 2003;Ledesma et al, 2013). When registering the months of May to August as the fruiting periods of guava, mango, Mexican plum and jobo, among other fruits in Nayarit as there is an increase in food availability, the populations of the insect pests increase and the probability of capture of the parasitoid decreases.…”
Section: Discussionmentioning
confidence: 99%